A randomized crossover trial assessing the effects of acute exercise on appetite, circulating ghrelin concentrations, and butyrylcholinesterase activity in normal-weight males with variants of the obesity-linked FTO rs9939609 polymorphism. Issue 5 (26th August 2019) - Dorling, James L; Clayton, David J; Jones, Jenny; Carter, Wayne G; Thackray, Alice E; King, James A; Pucci, Andrea; Batterham, Rachel L; Stensel, David J
ABSTRACT: Background: The fat mass and obesity-associated gene ( FTO ) rs9939609 A-allele is associated with higher acyl-ghrelin (AG) concentrations, higher energy intake, and obesity, although exercise may mitigate rs9939609 A-allele–linked obesity risk. Butyrylcholinesterase (BChE) hydrolyzes AG to des-acyl-ghrelin (DAG), potentially decreasing appetite. However, the effects of the FTO rs9939609 genotype and exercise on BChE activity, AG, DAG, and energy intake are unknown. Objective: We hypothesized that individuals homozygous for the obesity-risk A-allele (AAs) would exhibit higher postprandial AG and energy intake than individuals homozygous for the low obesity-risk T-allele (TTs), but that exercise would increase BChE activity and diminish these differences. Methods: Twelve AA and 12 TT normal-weight males completed a control (8 h rest) and an exercise (1 h of exercise at 70% peak oxygen uptake, 7 h rest) trial in a randomized crossover design. A fixed meal was consumed at 1.5 h and an ad libitum buffet meal at 6.5 h. Appetite, appetite-related hormones, BChE activity, and energy intake were assessed. Results: AAs displayed lower baseline BChE activity, higher baseline AG:DAG ratio, attenuated AG suppression after a fixed meal, and higher ad libitum energy intake compared with TTs [effect sizes (ESs) ≥ 0.72, P  ≤ 0.049]. Exercise increased Δ BChE activity in both genotypes (ESs = 0.37, P  = 0.004); however, exercise lowered AG and the AG:DAG ratio to a greater extent in AAs ( P  ≤ 0.023), offsetting the higher AG profile observed in AAs during the control trial (ESs ≥ 1.25, P  ≤ 0.048). Exercise did not elevate energy intake in either genotype ( P  = 0.282). Conclusions: Exercise increases BChE activity, suppresses AG and the AG:DAG ratio, and corrects the higher AG profile observed in obesity-risk AA individuals. These findings suggest that exercise or other methods targeting BChE activity may offer a preventative and/or therapeutic strategy for AA individuals. This trial was registered at clinicaltrials.gov as NCT03025347.